Polar ionospheric responses to solar wind IMF changes - Y. Zhang (Annales Geophysicae, 2000)
Auroral and airglow emissions over Eureka (89° CGM) during the 1997-98 winter show striking variations in relation to solar wind IMF changes. The period January 19 to 22, 1998, was chosen for detailed study, as the IMF was particularly strong and variable. During most of the period, Bz was northward and polar arcs were observed. Several overpasses by DMSP satellites during the four day period provided a clear picture of the particle precipitation producing the polar arcs. The spectral character of these events indicated excitation by electrons of average energy 300 to 500 eV. Only occasionally were electrons of average energy up to ~1 keV observed and these appeared transitory from the ground optical data. It is noted that polar arcs appear after sudden changes in IMF By, suggesting IMF control over arc initiation. When By is positive there is arc motion from dawn to dusk, while By is negative the motion is consistently dusk to dawn. F-region (anti-sunward) convections were monitored through the period from 630.0 nm emissions. The convection speed was low (100-150 m/s) when Bz was northward but increased to 500 m/s after Bz turned southward on January 20. Key words: Atmospheric composition and structure (airglow and aurora) - Ionosphere (particle precipitation) - Magnetospheric Physics (polar cap phenomena)